Avaliação do efeito da suplementação com benfotiamina sobre o desempenho aeróbio de corredores amadores - LEÃO, Renata Campos (2016)
Vitamin B1 (thiamine) is required in early stages of aerobic metabolism of glucose for the formation of adenosine triphosphate (ATP), that all cells of the body use as an energy source. Benfotiamine is a synthetic analogue of thiamine, that is dephosphorylated becoming it more lipid soluble and bioavailable. The aim of this study was to evaluate the effect of acute and chronic supplementation with benfotiamine in amateur athletes to verify its beneficial effect on physical performance. These are two randomized clinical trials, double-blind and crossover. The chronic assay was conducted with 10 runners amateurs who received daily supplementation with benfotiamine capsule (150 mg) or placebo for 1 month and after 1 month of washout intervention the assay was inverted. Another 10 runners amateurs received supplementation or placebo for two days, and then of washout intervention for 1 month, the assay was inverted. Among the results of the study, it was found that feeding of the runners is deficient in energy, macro and micronutrients. In addition, significant differences were found in chronic experiment, comparing the groups placebo and supplemented. Parameters such maximum oxygen consumption (VO2max) (p <0.031), the maximum volume of carbon dioxide (VCO2max) (p <0.043) and the ventilatory equivalent (VE / VO2) (p <0.034) were higher in the supplemented group. With the analyzes was concluded that chronic supplementation with benfotiamine has positive influence on oxidative metabolism.